Relations between philosophy and modern science on the example of the writings of Werner Heisenberg - Sobkowiak, Sebastian (Filozofia Chrześcijańska, 2019)
The article aims at presenting the relationship between science and philosophy based on the works of Werner Heisenberg. It deals with the infl uence of the scientifi c breakthrough on the understanding of physical concepts such as matter, time and causality. It also contains a discussion on the process of creating a new branch of science – quantum mechanics, and shows how the work and views of Heisenberg contributed to it. The relationship between physics and philosophy is presented here with particular emphasis on showing the results of research and philosophical refl ections on the concepts of matter, the philosophy of the language of science, the theory of unifi cation and the fl agship work of Heisenberg: the principle of uncertainty.